IMPLEMENTASI PERATURAN MENTERI SOSIAL NOMOR 1 TAHUN 2018 TENTANG PROGRAM KELUARGA HARAPAN DI DINAS SOSIAL KOTA PALEMBANG (STUDI KASUS PASAL 8 DI KECAMATAN ILIR BARAT II) - Effendi, Zulkani; Husin, Mansyur (Jurnal Ilmiah Administrasi Dan Sosial, 2023)
This study about the hope family program. Is one of Government program the seven to overcome povety.Through the fields of health and education. Palembang city,south sumatra willbe distributed by PT Pos indonesia the source of  PKH funds comes from APBN and APBD. Characteristics of those who receive APBD funds. Participation of this program is poor families with dependent children, pragnant women until puerperium, and fist year school age children, PKH field heath is a program that dimenkestrans and dinkes. The purpose of pkh among other things, it can quality of human resources, especially from very poor families.Keywords: implementation hope family program, Transactional, Social Services